Frontal Lobe and Psychoanalysis - Beteta Pacheco, Edmundo (1994)
Through an attractive hypothesis of work, we present the relaTionship between the frontal lobes and the neurobiological bases of Freud's psychoanalytic theory. We review and discuss the psycophysiological and clinical aproachs, in order to understand this relationship, arriving to the final examination of the organic and functional "disolutions" of the brain. We study and discuss the clinical progressive symptoms of the dementia and the differencial diagnosis of abnormal behavior, inrerpreted under the bases of Freud's theory. In this way it would be possible to arrive through some tempting interpretation of the psychopatic behavior, drug addiction and the last "syndrome of terrorism".